Bioinputs for sustainable nematode management in Brazil: Efficacy, challenges, and policy perspectives - Marques, Giovana Cândida; Bellato, Gustavo Ferreira; Moreira, Bruna Rodrigues; Bernardes Neto, José Feliciano (Multi-Science Journal, 2026)
The intensification of nematode-related losses in Brazilian agriculture has renewed interest in sustainable management strategies based on bioinputs. This systematic review (2018–2024) compiled 48 peer-reviewed studies from Scopus, Web of Science, SciELO, and the CAPES Journals Portal to evaluate the efficacy and limitations of microbial and botanical bioinputs against plant-parasitic nematodes. The main biological agents identified (Trichoderma spp., Bacillus spp., Pochonia chlamydosporia, and Purpureocillium lilacinum) act through parasitism, antibiosis, competition, and induction of systemic resistance, resulting in population suppression of Meloidogyne, Pratylenchus, and Heterodera species. Reported outcomes include up to 70% reduction in root-gall formation, improved root architecture, and 15–25% yield increases in tomato, soybean, and cotton. Nonetheless, field performance remains inconsistent due to environmental variability, formulation stability, and the need for more context-specific recommendations despite the recent expansion of product registration in Brazil. Evidence indicates that the integration of bioinputs with cultural and genetic tactics, such as crop rotation, resistant cultivars, and soil-health management, maximizes their efficiency. Under Brazil’s National Bioinputs Program (Decree No. 10.375/2020) and the Bioinputs Law (Law No. 15.070/2024), scaling these technologies depends on formulation advances, context-specific protocols, and stronger extension services. Overall, bioinputs represent an effective and environmentally safe component of integrated nematode management, linking productivity gains with sustainability and soil conservation.